2016
DOI: 10.1111/jpn.12429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cerium oxide supplementation to laying hen diets on performance, egg quality, some antioxidant enzymes in serum and lipid oxidation in egg yolk

Abstract: This study was conducted to determine the effects of dietary cerium oxide levels (0, 100, 200, 300 or 400 mg/kg) on the laying performance, egg quality, some blood serum parameters and egg lipid peroxidation of laying hen. In total, one hundred and twenty 22-week-old brown Lohman LSL laying hens were randomly assigned to five groups equally (n = 24). Each treatment was replicated six times. Dietary supplementation of cerium oxide had no significant effect on feed intake and egg weight. The addition of cerium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
(11 reference statements)
1
20
1
Order By: Relevance
“…However, pre-treatment of nano-ceria significantly reduced the level. Bölükbaşı et al (2016) used different doses to see the effect of dietary cerium oxide on egg lying performance of hen and found significant increase in egg quality parameters. They further found decreased level of AST in dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, pre-treatment of nano-ceria significantly reduced the level. Bölükbaşı et al (2016) used different doses to see the effect of dietary cerium oxide on egg lying performance of hen and found significant increase in egg quality parameters. They further found decreased level of AST in dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…• Significantly increased in total tract digestibility of DM, CP, and GE Han and Thacker [48] REE, rare earth elements; DM, dry matter; ADG, average daily gain; CP, crude protein; GE, gross energy. [49] • Whereas in group supplemented with 500 mg/kg REE plasma Ca and P had significantly increased only during first month of the trial • No significant changes were reported in second month of the trial Bolukbası et al [52] REE, rare earth elements; SOD, superoxide dismutase; GPx, glutathione peroxidase; MDA, malondialdehyde.…”
Section: Dosementioning
confidence: 99%
“…Essential oils, pre-and probiotics, organic acids and enzymes currently successfully used instead of antibiotic feed additives. A number of rare earth elements (REE), including cerium, can be successfully used as a new natural supplement to the feed for improve animal productivity [2,6,17,18,22,23,24,86,87].…”
Section: Abstract: Nanoparticles Cerium Dioxide Biotransformation mentioning
confidence: 99%
“…The application of REE had positive results for poultry [6,12,18,21,82,83,84]. In these studies, the addition of different levels of rare earth elements (200, 400, 600 and 800 mg/kg) promoted a significant increase in egg production, egg weight and hatching eggs fertilization rate of 6-month-old laying hens [82].…”
Section: Abstract: Nanoparticles Cerium Dioxide Biotransformation mentioning
confidence: 99%
See 1 more Smart Citation